KNOWLEDGE, ATTITUDE AND PRACTICE OF GENERAL PROFESSIONALS REGARDING VITAMIN D (The Research of Medical Science Review, 2025)
Background: Affecting around 2 billion people globally, vitamin D shortage is a major international health concern. The sole vitamin the human body synthesizes; sunlight is the main source. Maintaining regular physiological activities depends mostly on vitamin D. Objectives: To evaluate general professionals—including educationists, engineers, lawyers, artists and designers—about vitamin D in District Peshawar in knowledge, attitude, and practice (KAP). Methodology: Over two months, general professionals aged 25–45 years in District Peshawar participated in a descriptive cross-sectional survey. Using a non-probability convenience sampling method, a 400 person computed sample size was achieved. Reliable and tested D-KAP-38 Questionnaire was used for data collecting. General professionals between the ages of 25 and 45 were included; those with significant injuries were omitted. SPSS version 25 was used for statistical investigation. Results: With a mean age of 35 years, the 400 participants comprised 59% ( 234) men and 41% ( 166) women. About general awareness on vitamin D, 48% (193) of participants exhibited inadequate understanding while 52% (207) showed good knowledge. Of the individuals in the attitude domain, 42% (168) showed a positive attitude and 58% (232) a poor attitude. Regarding vitamin D procedures, just 41% (165) displayed good practices while 59% (235) displayed poor practices. Conclusion: Although the general understanding of vitamin D among the professionals was really decent, their behavior and attitudes contradicted their knowledge. This disparity highlighted the necessity of focused awareness efforts and initiatives aiming at encouraging good attitudes and practical approaches concerning vitamin D.